The Use of Interactive Learning Video Amat Cantik To Enhance Pisa Based Cognitive Learning Outcomes and Science Literacy Skills of Grade VIII Students - Setyowati, Denok; Widayat, Edy; Huda, Nuril (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2023)
The Use of Interactive Learning Video Amat Cantik to Enhance PISA Based Cognitive Learning Outcomes and Science Literacy Skills of Grade VIII Students at UPTD SMPN 5 Camplong. Thesis. Master’s Program in Educational Technology, Faculty of Education, Universitas Dr. Soetomo. Supervisors: (I) Dr. Edy Widayat, M.Sc., (II) Dr. Nuril Huda, M.PdI. This research employs a quantitative approach with a quasi-experimental design, where the research sample is not selected randomly. Data collection is conducted through pre-tests and post-tests. The study is conducted in the experimental class, which receives treatment through the use of Interactive Learning Video Amat Cantik, compared to the control class using conventional learning media (images). The research results are analyzed using a T-paired test with a significance value below 0.05, indicating a difference between the class using the Interactive Learning Video Amat Cantik and the class using conventional media (images).